Analisis Pelaksanaan Pembelajaran Online Mata Pelajaran PPKn Pada Masa Pandemi Covid-19 Di SMP Negeri 16 Kota Jambi - Setiara, Neka; Anderson, Irzal; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2022)
The results of the initial observations of researchers during the pandemic period, SMP Negeri 16 Jambi City continued to carry out the teaching and learning process as usual, but by using an online learning system. This study aimed to analyze the implementation of online learning courses during the pandemic covid PPKn-19 in SMP 16 terkhususnya class IX D, F IX and IXG. This research was conducted with a qualitative procedure with data and data sources obtained from informants, namely PPKn teachers who teach in class IX D, IX F and IX G and 2 students in class IX D, 2 students in class IX F and 1 student in class IX G. at SMP Negeri 16 Jambi City, with data collection techniques in the form of interviews, observations, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. Based on the results of data analysis that has been carried out, the findings and conclusions of this study are as follows: (1) on the convenience of learning during the pandemic as time goes by, teachers and students have become comfortable and accustomed to online teaching and learning. (2) teachers' digital literacy skills are quite good. (3) the level of adaptation of students to online learning is very good even though there are obstacles but students can overcome them by themselves. (4) the adequacy of the devices used are quite capable, such as cellphones, computers/laptops,applications WhatsApp, Google Classmeet and Google Classroom, although there are still some students who do not have cellphones personal. (5) the internet connection for teachers and some students is adequate because they use facilities Wifi at home and get assistance quota from the government, while some of the other students still use quotas personally and do not get quotas from the government, especially transfer students. (6) the cost of online learning has been fulfilled, both from parents and from the government. (7) The comfort level of the application is very comfortable to use so that students can understand and understand the Civics material delivered by the teacher. (8) online commitment after the pandemic pandemic is not very attractive because teachers and students are more interested in learning offline or face-to-face.